Associations of physical activity with self-rated health and well-being in middle-aged Finnish men. Issue 2 (March 2015) - Engberg, Elina; Liira, Helena; Kukkonen-Harjula, Katriina; From, Svetlana; Kautiainen, Hannu; Pitkälä, Kaisu; Tikkanen, Heikki
Aims: We examined the associations of physical activity (PA) frequency with self-rated health (SRH), self-rated well-being (SRW) and depressive symptoms, in middle-aged men in Finland. Methods: The cross-sectional study comprised 665 men (mean age 41 ± 3 SD years; body mass index (BMI) 26.8 ± 4.2 SD kg/m 2 ), who had completed the screening questionnaire of an intervention for men with cardiovascular risk factors. Their weekly frequency of PA was assessed by a questionnaire, SRH and SRW by visual analog scales (VAS), and depressive symptoms by the Patient Health Questionnaire-2 (PHQ-2). Results: The mean SRH ± SD (range of scale 0–100) by PA frequency categories was 56.2 ± 18.5 for PA sometimes or never, 63.8 ± 16.2 for PA about 1–2 times/week, and 71.1 ± 15.5 for PA at least 3 times/week. The mean SRW ± SD (range of scale 0–100) was 59.0 ± 20.4, 65.6 ± 17.6, and 68.9 ± 17.1, respectively. The mean PHQ-2 score ± SD (range of scale 0–6) by PA categories was 1.83 ± 1.40 for PA sometimes or never, 1.68 ± 1.28 for PA about 1–2 times/week, and 1.60 ± 1.31 for the PA at least 3 times/week group. SRH and SRW improved linearly with increasing PA frequency (both p < 0.001), and the results remained similar after adjustment for BMI, education and smoking status. No association existed between PA frequency and PHQ-2. Conclusions: More frequent PA was linearly associated with better SRH and SRW, but not with depressive symptoms that were measured by a brief depression screening tool.